Used of partographs in women in labour at Mulanje District Hospital in Malawi - Jere, Joyce Atuweni (My University, 2014)
Introduction: A partograph is a tool that is used to monitor progress of labour, and its correct use and appropriate interpretation can assist in early identification of complications of labour. The aim of this study was to assess if and how the partograph was used at Mulanje District Hospital in Malawi. Methods: This was a retrospective review of records of women who delivered at the Mulanje District hospital from the 1st to the 30th of September, 2010. A total of 360 women’s files were reviewed. Data was collected from the delivery register, theatre register, case files and partograph charts. A Chi-square was used for statistical analysis and a p value of < 0.05 was considered significant. Results: The partographs were available in 93.3% (336/360) of women’s files. Forty eight percent (162/336) of women’s files had partographs with all three sections of labour monitoring documented, but only 10% (16/162) of the partographs had information correctly and completely filled in on each parameter of the three components of the partograph. Forty percent (64/162) of women delivered after crossing the action line, and 67.2% (43/64) who delivered after crossing the action line were referrals, while 32.8% (21/64) were women who came to the hospital in labour. Almost 40.6% (26/64) of women who crossed the action line suffered immediate adverse outcomes. There was no significant difference in maternal outcomes (post partum haemorrhage, ruptured uterus and maternal deaths) and foetal outcomes (low Apgar score of 5/10 or less at 1 minute and 5 minutes, fresh still births and deaths within 24 hours) between women that were from the primary care health centres and those that reported to the hospital in labour. The study found that 57.8% (37/64) of women who crossed the action line had spontaneous vertex delivery, almost 38% (24/64) delivered by caesarean section and 4.7% (3/64) delivered by assisted vacuum extraction. There was a significant difference in mode of delivery after v crossing the action line. More caesarean sections were performed on women from the primary care health centres as compared to those that came to the hospital in labour: 44.2% (19/43) vs 23.8% (5/21), p=0.049. Conclusion and Recommendation: Although partographs were available in women’s files, the partograph data were not completed adequately. While progress of labour was frequently documented, maternal and foetal condition were incompletely documented. Effective interventions such as in-service training, regular supportive supervision, regular audits of records of women in labour and intensification of use of guidelines for labour management are required to strengthen the use of the partograph for women in labour. Further research is recommended to highlight barriers for correct use of the partograph
A Research Report submitted to the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, South Africa, in partial fulfilment of the requirements for the Degree of Master of Public Health - Maternal and Child Health Submitted: August 2014
Keywords: Labor, Obstetric